THE SHOCKING TRUTH—TIME BETWEEN DEFIBRILLATION ATTEMPTS DURING PRE-HOSPITAL RESUSCITATION OF VF CARDIAC ARREST. Issue 9 (14th August 2014) - Mitchell, Kirsty; Short, Steven; Clegg, Gareth
Abstract : Objectives & Background: Timely defibrillation and high-quality cardiopulmonary resuscitation (CPR) are the only pre-hospital interventions which have been demonstrated to save lives after OHCA (out-of-hospital cardiac arrest). Standard resuscitation using the advanced life support (ALS) algorithm specifies a period of two minutes of CPR after delivering a shock before re-assessing the rhythm and delivering a further shock if indicated. Recent work has focused on improving quality of CPR, but few studies have examined how effectively defibrillation is carried out in pre-hospital practice. This study aims to assess the timing of shocks during resuscitation after OHCA. Methods: Defibrillator (Philips MRX) data is routinely downloaded after all OHCA in Edinburgh as part of routine audit. We analysed a consecutive series of arrests 1-April-2013 and 31-March-2014. Only arrests where >1 consecutive shocks were delivered were included, in order to allow inter-shock intervals to be calculated. Event Review Pro software (Philips) was used to visualise ECG and CPR data, to determine time between shocks with no interrupting period of non-shockable rhythm. Inter-shock intervals between 2:00 min and 2:30 min were deemed compliant with ALS guidelines. Results: There were 189 cardiac arrests in the study period, with 70 cases eligible for inclusion. Mean time between shocks was 3:06 min (0:15 min–18:23 min, SD 1:54 min). 53% of inter-shock intervals were >2:30 min and 21% were <2:00 min. Only 26% of intervals were compliant with ALS guidelines. Figure 1 shows a scatter plot of the inter-shock intervals for each OHCA resuscitation episode. The red bar indicates the 'compliant' zone of 2:00–2:30 min. Conclusion: The majority of intervals between shocks delivered in out-of-hospital cardiac arrest were non-compliant with current ALS guidelines. Whilst the underlying reasons for this finding remain unclear, the extreme outliers appeared to be related to transporting the patient from the scene of the arrest. It was still the case, however, that the majority of defibrillation attempts were delivered either earlier than 2 min or later than 2:30 min, which may reflect a loss of situational awareness in the distracting environment of an OHCA resuscitation. Further work needs to be done to establish the cause of this deviation from recommended shock timing in order to develop strategies to optimise practice.